Ελληνικά μουσεία (Virtual Reality S.A., [Αποκλειστική διάθεση: MLS Multimedia], 1998)
Presentation of nine of the most important greek museums: the National Archaeological Museum, the Acropolis Museum, the Byzantine Museum in Athens, Thessaloniki Archaeological Museum, Ancient Pella in Northern Greece, Delphi Museum, Olympia Archaeological Museum, Herakleion Museum and Cyprus Museum.